IMPLEMENTASI FATWA DSN-MUI N0.96/IV/2015 TENTANG TRANSAKSI LINDUNG NILAI PADA TRANSAKSI FORWARD EXCHANGE CONTRACT - Amin Fauzi; Rachmat Adji Fahreza (Ekonomi Islam, 2018)
The purpose of this research is to know the Implementation of Fatwa DSN-MUI NO. 96/DSN-MUI/IV/2015 Concerning Hedging Transactions on Forward Exchange Contract.The data used are primary and secondary data. Primary data is the source of research data obtained directly from original sources in the form of interviews, opinions of individuals or groups and the results of observation. Secondary data is the source of research data obtained through intermediate media, books, records, and archives published or not published in general. According to the fatwa No. 96/DSN-MUI/IV/2015 about sharia hedging the conclusion of this study is forward exchange contract transactions not in a accordance with Islamic shari’a. DSN-MUI asserted that the concept of wa’ad must occur between the two parties who are bound by the transaction agreement, it is different from the Forward Exchange Contract that only uses the concept of single wa’ad (one party is bound) only.Islamic banks also have difficulty in determining the status or hedging transactions in Forward Exchange Contract. In addition, the implementation of the fatwa DSN-MUI on sharia hedge is still limited in certain areas only.